FRI0716 Risk stratification in young patients with acute myocardial infarction using the adjusted global antiphospholipid syndrome score (AGAPSS). (15th June 2017) - Radin, M; Schreiber, K; Costanzo, P; Cecchi, I; Roccatello, D; Baldovino, S; Bazzan, M; Cuadrado, M; Sciascia, S
Abstract : Background: Young adults with acute myocardial infarction are a critical group to examine for the purpose of risk factors stratification and modification [1]. In the setting of underlying systemic autoimmune diseases, premature cardiovascular disease deserves even more attention in these conditions, such as antiphospholipid syndrome (APS), the most common acquired thrombophilia. Objectives: In this study we aimed to assess the clinical utility of the adjusted Global AntiphosPholipid Syndrome Score (aGAPSS)[2] for the risk stratification of acute myocardial infarction in a cohort of young APS patients with thrombotic events. Methods: The analysis included 83 consecutive APS patients (≤50 years old) who presented with arterial or venous thromboembolic events. Data on cardiovascular risk factors and antiphospholipid antibodies (aPL) positivity were retrospectively collected. The aGAPSS was calculated for each patient by adding the points corresponding to the risk factors, based on a linear transformation derived from the β regression coefficient as follows: 3 for hyperlipidaemia, 1 for arterial hypertension, 5 for aCL IgG/IgM, 4 for anti-b2 glycoprotein I IgG/IgM and 4 for LA. Results: Demographic, clinical and laboratory characteristics of the cohort are summarized in Table 1 . Higher aGAPSS values were observed in patients with acute myocardial infarction when compared to the others [mean aGAPSS 11.9 (S.D. 4.15, range 4–18) Vs. (mean aGAPSS 9.2, S.D. 5.1, range 1–17); T test: p<0.05]. Significantly higher aGAPSS values were also seen in patients with acute coronary syndrome compared to patients with a history of peripheral or cerebrovascular arterial thrombotic events [mean aGAPSS 11.9 (S.D. 4.15, range 4–18) Vs. (mean aGAPSS 6.7, S.D. 5.7, range 1–17); T test: P<0.005]. When separating for cardiovascular risk factors and aPL positivity, hypercholesterolemia was significantly higher in the group that developed myocardial infarction compared with patients with a history of any thrombosis and patients with a history of peripheral or cerebrovascular arterial thrombotic events (Chi square test: p<0.0001 and p<0.0001) and significantly higher rate of multiple positivity for LA, aCL (IgG/IgM), anti-β2GPI antibodies (IgG/IgM) were present in the group that developed myocardial infarction (Chi square test: p<0.05 for all aPL) (Table 2). Conclusions: The aGAPSS is based upon a quantitative score and could aid risk stratifying APS patients younger than 50 years for the likelihood of developing coronary thrombotic events and may consequently guide pharmacological treatment for high-risk patients. References: Zimmerman FH, Cameron A, Fisher LD, Ng G. Myocardial infarction in young adults: angiographic characterization, risk factors and prognosis (Coronary Artery Surgery Study Registry). J Am Coll Cardiol 1995;26:654–61. Sciascia S, Sanna G, Murru V, Roccatello D, Khamashta MA, Bertolaccini ML. GAPSS: the Global Anti-Phospholipid Syndrome Score. Rheumatology (Oxford) 2013;52:1397–403. doi:10.1093/rheumatology/kes388. Acknowledgements: None. Disclosure of Interest: None declared